Popular fear and distrust of a hospital dubbed 'Slagpale' : an ethnography of gossip and rumour in former KwaNdebele, South Africa - McNeill, Fraser G. (University of Pretoria, 2018)
Dissertation (MSocSci)--University of Pretoria, 2018.